Prevalence of Urinary Incontinence among married females in Sialkot Pakistan: Prevalence of Urinary Incontinence among married females in Sialkot Pakistan - Amanat Ali, Misbah; Naeem, Laiba; Asif, Roha; Imran, Komal; Noor, Momna; Hafeez, Mahrukh (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Impairment in the pelvic floor muscles and nerves that control the continence of urine can occur due to various conditions in the women, which may affect the lifestyle of women. Objective: To find the prevalence of Urinary Incontinence in married females in Sialkot. Methods: This observational study was conducted at public and private settings of Sialkot in six months after ethical approval. A sample of 100 married females was targeted through non-probability convenient sampling. ICIQ-UI (International Consultation on Incontinence Questionnaire) short form questionnaire was used to collect the data. Middle aged women (35-55Years) were included, while unmarried females, pregnant females, females with any history of spinal cord injury and other comorbid conditions were excluded. Results are expressed as frequencies and percentages using IBM Software SPSS Version 20.0. Results: Mean age± SD of the participants was 38.4±6.615 years. While calculating the amount of urine leaking; 16% (n=16) had none, 57% (n=57) had a small amount, 25% (n=25) had a moderate amount and 2% (n=2) had a large amount. Similarly, interference with everyday life due to leaking urine was found in 79% (n=79) mild to moderate, 16% (n=16) not at all interferes and 5% (n=5) were greatly interfered. Mean ICIQ-UI score± SD was 9.53±0.36 ranging from 0-11. Most of the women reported urine leakage in a small amount, once a day effecting mild to moderately their daily livings usually due to coughing, sneezing or physical activity Conclusions: Most of the females have episodic urinary incontinence mostly associated with cough, sneeze and physical activity.